Digging down under: Australian Bolboceratini, their habits and a list of species (Coleoptera: Scarabaeoidea: Geotrupidae) - Howden, Henry; Howden, Anne; Holloway, Geoffrey (Zootaxa, 2007)
The adult habits of the ten genera of Australian Bolboceratini (Scarabaeoidea, Geotrupidae: Bolboceratinae) are briefly discussed, mentioning at least one species in each genus. Morphological variation, food, and/or predation are described for some species. The eggs and larvae of Bolborhachium anneae Howden are discussed and pictured. A picture of one of the fungi used for adult food is included and one of push-ups marking burrows. The Australian species of Bolboceratini described through 2006 are listed.